Application of a UPLC‐MS/MS method for the analysis of alosetron in human plasma to support a bioequivalence study in healthy males and females. (11th March 2015) - Chaudhary, Darshan V.; Patel, Daxesh P.; Shah, Jaivik V.; Shah, Priyanka A.; Sanyal, Mallika; Shrivastav, Pranav S.
ABSTRACT A simple, rapid and sensitive ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method has been developed and validated for the determination of alosetron (ALO) in human plasma. The assay method involved solid‐phase extraction of ALO and ALO 13C‐d3 as internal standard (IS) on a LichroSep DVB‐HL (30 mg, 1 cm3) cartridge. The chromatography was performed on an Acquity UPLC BEH C18 (50 × 2.1 mm, 1.7 µm) column using acetonitrile and 2.0 mm ammonium formate, pH 3.0 adjusted with 0.1% formic acid (80:20, v/v) as the mobile phase in an isocratic mode. For quantitative analysis, the multiple reaction monitoring transitions studied were m/z 295.1/201.0 for ALO and m/z 299.1/205.1 for IS in the positive ionization mode. The method was validated over a concentration range of 0.01–10.0 ng/mL for ALO. Post‐column infusion experiment showed no positive or negative peaks in the elution range of the analyte and IS after injection of extracted blank plasma. The extent of ion‐suppression/enhancement, expressed as IS‐normalized matrix factor, varied from 0.96 to 1.04. The assay recovery was within 97–103% for ALO and IS. The method was successfully applied to support a bioequivalence study of 1.0 mg alosetron tablets in 28 healthy Indian male and female subjects. Copyright © 2015 John Wiley & Sons, Ltd.